Kemampuan Ganoderma dan Trichoderma Mendekomposisi Serasah Acacia mangium (The Ability of Ganoderma and Trichoderma to Decompose Acacia mangium Litter) - Samingan SAMINGAN (Universitas Jambi, 2015)
Litter decomposition ability of fungi has an important role in forest floor ecosystem. The abilities of Ganoderma sp and Trichoderma sp to decompose Acacia mangium leaf litters at laboratory scale were observed. Litters from L and F layers in the field ca. 100 g were used as substrates in plastic bags. Each fungus was inoculating onto substrates and incubates at room temperature, then observed each month during six months. Weight losses (WL) of litter, lignin and cellulose contents during decomposition were measured. Colonization of Ganoderma in litter and PDA with litter powder were also observed. The results showed that WL of litters, lignin and cellulose by Ganoderma were low. WL of L and F litters were 3.99% and 4.57% respectively, while WL of L and F lignin were 8.17% and 7.11% respectively, and WL of L and F cellulose were 3.63% and F 2.59% respectively. WL of L and F litters by Trichoderma were 3.20% and 3.20% respectively, while WL of L and F lignin were 3.83% and 3.85% respectively, and WL of L and F cellulose were 2.43% and 3.17% respectively. The growth of Ganoderma was better at PDAS than that at PDA; therefore L litter layer was suitable for growing Ganoderma.